KAJIAN ATAS RISIKO KELOMPOK USIA DAN KLAIM RUMAH SAKIT (RS) COVID-19 DI INDONESIA, 2020 – 2021 - Maulana, Andhika Nurwin; Faizin, Ruli E Al; Komaryani, Kalsum; Purwaningrum, Farah; Thabrany, Hasbullah (Jurnal Ekonomi Kesehatan Indonesia, 2022)
This study measures the risk of age group and its correlation with severity level, length-of-stay (LOS), cost of treatment, and discharge of inpatient status. By ‘age group’ we refer to children, productive, and elderly. Since mid-2020 government of Indonesia opted for a micro lockdown in several areas to reduce pandemic transmission nevertheless ensure economic recovery. However, people will have a higher risk if they conduct economic activities, moreover if they were to take public transport to their workplace. We also measure several differences between the implementation of technical guidance of 4th and 5th had a more significant differences in LOS and inpatient’s hospital’s claim. This paper uses data from Ministry of Health (MoH) namely of around 207 thousand inpatient people of COVID-19 across all provinces in Indonesia from March 2020 to January 2021. This preliminary research result where children were the highest proportion recovered compared to working age group discharged status, and elderly age had the lowest proportion of recovered discharged status. While elderly was the highest died discharged status compared to working age group, and children had the lowest died discharged status. Result for regression almost all the independent variables were significant having impact to claims of COVID-19 claim.